Supporting hemodialysis patients: A phenomenological study - Nahid Shahgholian; Hojatollah Yousefi (Wolters Kluwer Medknow Publications, 2015)
Background: Chronic renal disease and hemodialysis cause numerous psychological, social, cultural, and spiritual challenges for both patients and their families. Overcoming these challenges is possible only through providing holistic support for the patients. Today, despite the support provided by family and professional caregivers for the patients, patients still express dissatisfaction with the support provided and believe it to be inadequate. In fact, patients and family caregivers and healthcare practitioners seem to have different understandings of the notion of support. Thus, the researcher decided to examine the concept of support from the viewpoint of hemodialysis patients. Materials and Methods: This descriptive phenomenological research was conducted on 17 patients with end-stage renal disease (ESRD) who were undergoing hemodialysis. Purposive sampling was performed and continued until data saturation. Data were collected through 30-60 min unstructured interviews and analyzed using Colaizzi's method. Results: From the analysis of data, 4 themes (psychological support, accompaniment, social support, and spiritual support) and 11 sub-themes were obtained. Psychological support consisted of two sub-themes of psychological support by healthcare practitioners and emotional support by family and relatives. Accompaniment included three sub-themes of assistance in transportation, providing and using medicine, and daily activities. Social support was identified with four sub-themes of promotion of the society's understanding of the patients' condition, improvement of communication with others, the need for employment, and independence. Spiritual support was identified with two sub-themes of the need for faith and trust in God or Imams and the need to resolve spiritual contradictions. Conclusion: The results showed that from the viewpoint of the participants, the concept of support consisted of psychological support, social support, accompanying the patient, and spiritual support. Hence, it can be concluded that this concept should be considered in healthcare planning, in order to improve the health and quality of life of these patients and their adaptation to the disease and its treatment process.